Dynamic modeling of a springboard during a 3 m dive - Haake, S.; Goodwill, S.; Heller, B.; Schorah, D.; Gomez, J. (Procedia Engineering, 2010)
Analysis of springboards in elite diving have been limited to the measurement of the variation of material characteristics along the length of the board and it appears that dynamic models of the board's motion have not been carried out because of its complex nature. The purpose of this paper is to develop a simple mechanical model to (i) understand the physics of the board's motion and (ii) act as a precursor to optimizing the board to enable divers to maximize their chances of a good score.